(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article examines the influence of information and communication technologies on the educational process of higher education. Based on the strategic tasks of the Higher Education Development Concept until 2030, the possibilities of modern forms of educational process organization and digital technologies were analyzed. The purpose of the ideas put forward in the article is to effectively use ICT opportunities and increase the quality of education.